2015
DOI: 10.3233/thc-150899
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study using the XBOX Kinect for exercise conditioning in sedentary female university students

Abstract: Engaging in dancing using dance videogames can lead to improved cardiovascular conditioning and flexibility in sedentary female university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…However, the magnitude of blood pressure response was significantly lower in the PLAY setting compared with AVG or tV after sessions. In a similar population to that in our study, female university students performed a 6-week training (30-60 minutes of Just Dance 4 game sessions) and, unlike our participants, reduced resting blood pressure [14]. Likewise, Warburton et al [13] identified a reduction in resting SBP of approximately 9 mm Hg among college boys who underwent a 30-minute AVG session (Cyclebike) for 6 weeks.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…However, the magnitude of blood pressure response was significantly lower in the PLAY setting compared with AVG or tV after sessions. In a similar population to that in our study, female university students performed a 6-week training (30-60 minutes of Just Dance 4 game sessions) and, unlike our participants, reduced resting blood pressure [14]. Likewise, Warburton et al [13] identified a reduction in resting SBP of approximately 9 mm Hg among college boys who underwent a 30-minute AVG session (Cyclebike) for 6 weeks.…”
Section: Resultssupporting
confidence: 59%
“…In fact, resting HR presented significant reduction after our intervention; hence, the decrease of DP, also observed after the intervention, was dependent on the HR changes. other studies also investigated the influence of AVG modalities on cardiovascular fitness by identifying a resting HR reduction [12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more precise a player is at replicating the dance moves the higher their scores. Unlike conventional dance training, the XBOX Kinect provides both intrinsic (visual, auditory, vestibular, somatosensory) and extrinsic (scores that rank performance, and indicators of accuracy of movement) feedback, which is ideal for motor learning (Roopchand-Martin, Nelson, Gordon, & Yee Sing, 2015). Research has shown that this type of training is acceptable to young persons and athletes (Adachai & Willoughby, 2014;Roopchand-Martin, Mason, & Gibson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…48 Self-efficacy was enhanced by showing an image of the player on the screen among those who had a positive self-image, but not among those who were dissatisfied with their self-image. 49 The technology of exergaming is rapidly advancing (e.g., Kinect) 50 augmented reality games, 51 Zombies Run (www .zombiesrungame.com), and smart watches with virtual sensor networks, 52 which can be linked to enhance exergaming. These technological advances offer exciting new opportunities for engaging children in exergaming.…”
mentioning
confidence: 99%